PAJAK DI ERA DIGITAL PENDEKATAN TAM (TECHNOLOGY ACCEPTANCE MODEL) PADA PELAPORAN SPT MENGGUNAKAN CORETAX DJP - Rasmon, Rasmon; Rahmad, Rinto; Yasid, Muhammad (Komunitas Manajemen Kompetitif, 2026)
This study is a quantitative research project aimed at determining the acceptance and usage of Coretax DJP using the Technology Acceptance Model. Sampling was conducted using random sampling, with a sample size of 39 practitioners who are alumni of the LKP Sahabat Prestasi Tax Brevet A & B programmes and who are currently employed by companies across Indonesia. Hypothesis testing in this study was carried out using SPSS Version 26. The results of the testing indicate that (1) computer proficiency influences perceived usefulness, (2) computer proficiency influences perceived ease of use, (3) perceived ease of use influences perceived usefulness, (4) perceived usefulness influences user attitude, and (5) perceived ease of use influences user attitude. It is hoped that this study will help to raise awareness that the use of technology is vital in the current era, where tax regulations are becoming increasingly dynamic and complex, necessitating an integrated system to ensure that tax reporting becomes more efficient and user-friendly.